Internet use and political participation: Engaging citizenship norms through online activities. Issue 2 (2nd April 2016) - Feezell, Jessica T.; Conroy, Meredith; Guerrero, Mario
ABSTRACT: Research on the relationship between Internet use and political participation has identified numerous effects that result from various online activities, though the mechanisms of influence often remain unclear. In response, we develop a theory of Internet effects and citizenship norms, wherein specific uses of the Internet influence political participation by fostering dutiful or actualizing norms of citizenship. Using a longitudinal research design comprised of five nationally representative, postelection surveys (2002–2010), we find that people who engage in dutiful uses are more likely to participate in the dutiful act of voting than those who engage in actualizing uses; these findings are most prevalent among those aged 18–30. These results suggest that online activities, which reflect specific norms of citizenship, often predict corresponding forms of political participation.